2020
DOI: 10.3897/zookeys.953.53175
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Oomyzus Rondani (Hymenoptera, Eulophidae) reared from the pupae of Coccinella septempunctata (Coleoptera, Coccinellidae) in China

Abstract: Oomyzus spiraculus Song, Fei & Cao sp. nov. (Hymenoptera, Eulophidae) is described and illustrated as a gregarious larval-pupal endoparasitoid of Coccinella septempunctata L. (Coleoptera, Coccinellidae). Differentiation between O. spiraculus and its similar species is discussed and a key to differentiate the female and male of these species is provided. DNA barcodes of O. spiraculus and O. scaposus are analyzed and compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…septempunctata , but rarely attack H . axyridis ( Song 2017 ; Song et al 2017 , 2020 ). In Western Siberia, the phorid parasitoid P. fasciata parasitized 45% of C .…”
Section: Interactions Within Native Range: Mechanisms Of Coexistencementioning
confidence: 99%
“…septempunctata , but rarely attack H . axyridis ( Song 2017 ; Song et al 2017 , 2020 ). In Western Siberia, the phorid parasitoid P. fasciata parasitized 45% of C .…”
Section: Interactions Within Native Range: Mechanisms Of Coexistencementioning
confidence: 99%
“…Some species are phytophagous, inquilines, or gall-formers (LaSalle, 1994). In China, 24 genera and 165 species of this subfamily are reported (Perkins, 1912;Timberlake, 1921;Miwa et al, 1935;Yoshimoto, 1970;Yang & Wei, 2003;Yang et al, 2003a,b;2005;Wu et al, 2001;Li, 2013;Li et al, 2014;Yang et al, 2014;Song et al,2014;Li et al, 2020;Song et al, 2020;Li, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With more research on parasitic wasps, Chinese entomologists realized the importance of this faunal group: Liao et al (1984) reported 201 economically important insect species of China including eight species of Tetrastichinae; Yang (1996) systematically investigated parasitic wasps on bark beetles from China and reported 141 species including 16 species of Tetrastichinae; Zhu and Huang (2001) investigated Eulophidae from Zhejiang province and reported 12 species of Tetrastichinae; Zhu and Huang (2002) investigated Eulophidae from Guangxi province and reported 23 species of Tetrastichinae; Zhang et al (2007) investigated Eulophidae from south Gansu and Qinlin Mountains and reported 14 species of Tetrastichinae; Yang et al (2015) systematically investigated parasitic wasps on forest defoliators, reporting 115 species including 20 species belonging to four genera of Tetrastichinae. Subsequently, there are many more reports of new species and records of Tetrastichinae (Yang 1989;Sheng andWang 1992, 1993;Sheng 1995;Sheng and Zhao 1995;Sheng and Zhu 1998;Yang and Wei 2003;Jiao et al 2006;Zhang et al 2009;Wu et al 2009;Li et al 2014;Yang et al 2014;Feng et al 2016;Li et al 2016;Song et al 2017;Li 2020, 2021;Song et al 2020;Guo et al 2022;Ning et al 2022). In terms of Tetrastichinae species richness, there is an obvious imbalance among provinces of China.…”
Section: Introductionmentioning
confidence: 99%